A cell type–specific approach to elucidate the role of miR-96 in inner ear hair cells - Gwilliam, Kathleen; Sperber, Michal; Perry, Katherine; Rose, Kevin P.; Ginsberg, Laura; Paladugu, Nikhil; Song, Yang; Milon, Beatrice; Elkon, Ran; Hertzano, Ronna (Frontiers in Audiology and Otology, 2024)
Introduction Mutations in microRNA-96 (miR-96), a microRNA expressed within the hair cells (HCs) of the inner ear, result in progressive hearing loss in both mouse models and humans. In this study, we present the first HC-specific RNA-sequencing (RNA-seq) dataset from newborn Mir96Dmdo heterozygous, homozygous mutant, and wildtype mice. Methods Bulk RNA-seq was performed on HCs of newborn Mir96Dmdo heterozygous, homozygous mutant, and wildtype mice. Differentially expressed gene analysis was conducted on Mir96Dmdo homozygous mutant HCs compared to wildtype littermate controls, followed by GO term and protein-protein interaction analysis on these differentially expressed genes. Results We identify 215 upregulated and 428 downregulated genes in the HCs of the Mir96Dmdo homozygous mutant mice compared to their wildtype littermate controls. Many of the significantly downregulated genes in Mir96Dmdo homozygous mutant HCs have established roles in HC development and/or known roles in deafness including Myo15a, Myo7a, Ush1c, Gfi1, and Ptprq and have enrichment in gene ontology (GO) terms with biological functions such as sensory perception of sound. Interestingly, upregulated genes in Mir96Dmdo homozygous mutants, including possible miR-96 direct targets, show higher wildtype expression in supporting cells compared to HCs. Conclusion Our data further support a role for miR-96 in HC development, possibly as a repressor of supporting cell transcriptional programs in HCs. The HC-specific Mir96Dmdo RNA-seq data set generated from this manuscript are now publicly available in a dedicated profile in the gene expression analysis resource (gEAR-https://umgear.org/p?l=miR96).